THE АNAPA AMPELOGRAPHIC COLLECTION IS THE LARGEST CENTER OF VINE GENE POOL ACCUMULATION AND RESEARCH IN RUSSIA - M. I. Pankin; V. S. Petrov; A. A. Lukianova; E. T. Ilnitskaya; G. E. Nikulushkina; A. G. Kovalenko; V. А. Bolshakov (Вавиловский журнал генетики и селекции)
Nowadays there is much tension in the Russian modern vine growing industry around the issue of enhancing the range of grape varieties, which is aimed at production of highly adaptive grape plants and sustainable production of competitive grape varieties in the unstable stressing weather conditions of the moderate continental climate in the south of Russia. In this view, we believe it important to carry out research into the origin, generation and preservation of genetic resources so that they can be involved in the selection process and reach most important objectives of the national economy. The role of a variety and ampelographic collections becomes more important. The Anapa ampelographic collection (http://azosviv.info/category/osnovnye_razdely/anapskaya_ampelograficheskaya_kollekciya) is Russia’s largest gene pool depository of grape varieties brought from various countries of Europe, Asia and America, and Russia’s regions as well. It contains 4921 grape varieties, including Vitis vinifera L. (2975), V. amurensis Rupr. (40), V. labrusca L. (50), the interspecies varieties V. vinifera L.×V. amurensis Rupr. (210), V. vinifera L.×V. labrusca L. (168), blended interspecies hybrids V. vinifera L.× hybrids SV (220), V. vinifera L.×V. amurensis Rupr.×hybrids SV (70), and other samples. We carry out extensive research into collection varieties for their production and selection. We select varieties and forms showing good agronomic characters in productivity, quality of grapes and wine products, winter hardiness, drought resistance, and resistance to pests. We have identified, preserved and now use in selection, as sources of good agronomic characters of resistance to low temperatures in winter, such varieties as Riesling of the Rhine, Rkatsiteli, Aligoté, Riesling of Italy, Traminer Pink, Pinot Noir, Rara Neagra, Cabernet Sauvignon, Coarna Neagra, Pinot Gris, Gamay Freaux, Saperavi, Muscat Ottonel, Madeleine Angevine, Cabernet Franc, Khikhvi, Pearl of Csaba, Chardonnay, Krasnostop of Anapa, Dostoiniy, Krasnostop AZOS, etc. The collection has given birth to twenty seven varieties and elite forms, of which twelve varieties have been sent to the State Committee for the Testing of New Varieties of Agricultural Plants (Pluto, Muzhestvenniy (Courageous), Gordiy (Proud), Maran, Varvarovsky, Harmony, Progress, Gorniy (Mountaneous), Saturn, Dimitry, Vladimir, Kurchansky). We carry out a molecular genetic testing of the accumulated gene pool and DNA-classification of varieties. We have studied the microsatellite polymorphism in the genotypes of autochthonous grape varieties of the Don River and the Republic of Dagestan. We are performing the DNA-classification of varieties selected by the North Caucasian Regional Research Institute of Horticulture and Viticulture (Krasnodar), which is advantageous for the identification of pure varieties in planting material and vineyards and specifying of the parent forms of grape varieties, as well as when any disputes arise as to the variety authorship.